Implementasi Metode Design Thinking pada Perancangan UI/UX Aplikasi FooYu: Future of Opportunities Youth University - Putri Dia Lestari (Prosiding SISFOTEK, 2025)
This paper presents the implementation of the Design Thinking method in designing the User Interface (UI) and User Experience (UX) of FooYu, a mobile application developed to connect students and alumni of UPN “Veteran” Jawa Timur with career opportunities and freelance projects. The research applies five stages of Design Thinking, namely Empathize, Define, Ideate, Prototype, and Testing. During the Empathize stage, user interviews were conducted to identify needs and challenges. The findings were translated into design requirements in the Define stage, while the Ideate and Prototype stages focused on generating and visualizing creative solutions using Figma. The Testing stage utilized the System Usability Scale (SUS) to measure usability, yielding a score of 34.5, indicating that the application demonstrates good usability. The results show that Design Thinking effectively supports user-centered product design, leading to a more intuitive and accessible interface for novice freelancers.